Torque creation and force variation along the cutting edges of Acheulean handaxes: implications for tip thinning, resharpening and tranchet flake removals. (August 2020) - Key, Alastair; Lycett, Stephen J.
Abstract: One of the defining characteristics of Acheulean handaxes is the presence of a substantial length of sharp cutting edge, often covering the majority or entirety of their plan-form outline. Recently, factors affecting the efficiency and effectiveness of handaxes for cutting have come under increased scrutiny. Most studies investigate how shape, size, symmetry and other metrics influence cutting performance characteristics. This includes investigations of edge morphology. To date, it is unknown how cutting performance may vary within an individual handaxe dependent on which aspect of its edge is used. Here, we experimentally investigate how loading capabilities (applied forces) vary along the edges of handaxes, from tip to base. Significant differences were identified dependent on the edge-point loaded, with greater forces recorded at the tip of tools relative to more proximally located edges. Notably, at 20% of a handaxe's length away from the tip, loading levels were reduced by around 24%. Acheulean hominins concerned with maximising cutting stress potential during tool use should, therefore, have preferentially used the tip portion of handaxes when possible. During broader, sweeping cutting motions that use substantial lengths of cutting edge, our data suggest different portions of the edge create variable cutting-stress levels. Such differences likely derive from increases and decreases in torque creation, and the interaction between cutting forces and ergonomic relationships at the hand-tool interface. We discuss how these relationships may have influenced handaxe design during the Acheulean period, including tip focused modifications such as tranchet flake removals, thinning, and increased resharpening. Highlights: Using a substantial replica toolset (n = 457), we assess how loading potential varies along the edge of handaxes. Differences were identified dependent on the edge-point loaded, with greater force recorded at the tip of tools. Hominins concerned with maximising cutting stress potential should have preferentially used the tip portion of handaxes. These differences derive from variation in torque creation, and ergonomic relationships at the hand-tool interface. Modifications such as tranchet flake removals, thinning and resharpening may have been influenced by this relationship.